Development of process protocol for garcinia cambogia power - Sunitha C P (Department of postharvest technology and agricultural processing, Kelappaji College of Agricultural Engineering and Technology, 2012)
The major problem faced by the farmers regarding the processing of Garcinia cambogia is difficulty in drying of this fruit as the harvesting period coincides with the southwest monsoon also if not processed quickly fungal infection may takes place. And the currently adopted sun drying method takes long time and affects the quality of the product. Drying of Garcinia cambogia juice into powdered particles gives a considerable reduction in volume, easy to use and is an effective method for prolonging the shelf life. Therefore, a research study was conducted to develop a process protocol for Garcinia cambogia powder from the fresh fruit itself. Powder samples were obtained by drying the Garcinia cambogia juice using spray dryer (atomizer speeds 17000rpm and 22000rpm, inlet air temperature 175 and 180oC and feed flow rates 5, 5,5 and 6 l/h), tray drying (at 60, 70 and 80oC) and vacuum tray drying (40, 45 and 50oC) techniques. Garcinia cambogia juice at 120brix was used to prepare the fruit juice powder. In order to reduce the stickiness and also to increase the yield of the powder, maltodextrin (15% based on sensory evaluation, moisture content and solubility) the most widely used additive was used. The method of drying parameter was optimized on the basis of quality of the powder such as moisture content, total solids, colour, acid value, pH, bulk density solubility index and wettability. The quality of the powder obtained using spray dryer at an inlet air temperature of 1800 C, speed of the atomizer 22000 rpm and feed rate as 5.5 l/h (with an average particle size (8 μm), bulk density (0.412 3 g/cm ), moisture content (3.5939%wb) and total solids (96.407) was superior to those obtained by vacuum tray dried and tray dried product. So spray drying was selected as the best method for the production of Garcinia cambogia powder which have a storability of above 7 months with good reconstitution properties (wetting time, 80 S) and solubility index ,<0.1mm ).